Reading, Writing and the “Straight White Male”: What Masculinity Studies Does to Literary Analysis - Pierre-Antoine Pellerin (Angles)
This article aims at mapping out some of the ways in which masculinity studies has recently renewed the critical approach to certain literary texts. It argues that this fairly new disciplinary field has helped to de-territorialize literary inquiry and challenges deep-rooted assumptions about reading and writing. Essentialist notions like “masculine writing,” bodily analogies between the pen and the phallus, and psychoanalytical tools such as the Oedipus myth have tended to obfuscate the multitude of masculine identities at work in literature. Combined with the textual and performative approach developed by queer theorists, the work done by historians of masculinity enables, for instance, to shed light on the pressures that burdened authorial identity in a context of homophobia like the Cold War period in the United States, to delineate the ways in which the constitutive homosociality of poetic circles in the 1950s fashioned their aesthetic norms and practices, and to deconstruct the narrative codes and the fictions of masculinity which structured certain literary genres like the crime novel and the adventure novel.